La Mostra d'Oltremare nella Napoli occidentale Ricerche storiche e restauro del moderno - Aveta, Aldo (Fuori Collana, 2021)
The present work was born with a twofold objective: to go deeper into the knowledge of an urban landmark and, at the same time, to outline a future scenario aligned to its value, starting from a proper recovery of the multiform and valuable architecture that compose it. The deepening arises from the need to study multiple actions and themes: to examine the background project of the Mostra d'Oltremare identified in the new studies, not only in the city debate on a suitable space for exhibitions to be preferably located to the west, but also in authorial preliminary solutions, until now unknown, which have conditioned the final conformation; to highlight the specificity of the single elements of the complex, the survived and the disappeared ones, without limiting the study to the best known and most celebrated cases, but also to the less investigated and difficult to interpret ones, without neglecting the open spaces and the green areas; to deepen also those architectures that cannot be interpreted in the line of modernity but equally emblematic of that phase, therefore worthy of preservation; not limiting attention to the heroic, albeit debatable, phase of the first foundation, but analyzing with the same acumen the subsequent ones, starting with the problematic reconstruction and redefinition of the post-war period; not stopping at the systematic reconnaissance of indirect sources that have not been investigated until now - from the many archives, not only on a city but also on a national scale, to the newspapers and the press of the time - but questioning the same material consistency of the buildings with a scientific method; finally, not focusing only on the past and on the history of the Exhibition and of the single architectures, but projecting it into the future by identifying the best strategies of recovery, restoration and preservation.